2021
DOI: 10.1093/narcan/zcab036
|View full text |Cite
|
Sign up to set email alerts
|

Regulatory roles of RNA modifications in breast cancer

Abstract: Collectively referred to as the epitranscriptome, RNA modifications play important roles in gene expression control regulating relevant cellular processes. In the last few decades, growing numbers of RNA modifications have been identified not only in abundant ribosomal (rRNA) and transfer RNA (tRNA) but also in messenger RNA (mRNA). In addition, many writers, erasers and readers that dynamically regulate the chemical marks have also been characterized. Correct deposition of RNA modifications is prerequisite fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 202 publications
0
18
0
Order By: Relevance
“…The deposition of chemical modifications into RNA has recently emerged as a source of ribosome heterogeneity and constitutes a mechanism for rapid adaptation to changing environmental cues ( Gay et al., 2021 ). Such adaptation is crucial for cellular homeostasis, and dysregulated RNA modification pathways in humans have been linked to tumorigenesis ( Kumari et al., 2021 ). A recently constructed rRNA 2′O-methylation landscape of primary human breast tumors uncovered the existence of stable and variable modification sites ( Marcel et al., 2020 ).…”
Section: Resultsmentioning
confidence: 99%
“…The deposition of chemical modifications into RNA has recently emerged as a source of ribosome heterogeneity and constitutes a mechanism for rapid adaptation to changing environmental cues ( Gay et al., 2021 ). Such adaptation is crucial for cellular homeostasis, and dysregulated RNA modification pathways in humans have been linked to tumorigenesis ( Kumari et al., 2021 ). A recently constructed rRNA 2′O-methylation landscape of primary human breast tumors uncovered the existence of stable and variable modification sites ( Marcel et al., 2020 ).…”
Section: Resultsmentioning
confidence: 99%
“…In the last decade, m 6 A has been established as an important layer of post-transcriptional control of gene expression, and its dysregulated deposition has been defined to be critical for breast cancer initiation, progression and metastasis (43). Although several studies have shown the role of m 6 A in splicing regulation (9,25,38,41,58), to our knowledge, the function of m 6 A in breast cancer-associated AS switches has not been reported yet.…”
Section: Discussionmentioning
confidence: 99%
“…On the contrary, another study reported that not only METTL3 but also other members of the writer complex such as METTL14 and WTAP are downregulated in breast cancer, suggesting that lower levels of m 6 A may contribute to breast tumorigenesis (47). Similar contradictory findings are observed for other players of m 6 A modification, being writers, erasers or readers of m 6 A up-or downregulated depending on the cellular context (43,44). Mechanistically, m 6 A may dictate the fate of tumor suppressor or oncogenic transcripts (e.g., BCL2, BNIP3, c-MYC, CXCR4, and CYP1B1), influence the treatment outcomes (e.g., resistance to tamoxifen or doxorubicin via methylation of AK4 or miRNA-221-3p) or regulate the stability of pluripotency factors (e.g., Nanog and KLF4), thus facilitating epithelial-mesenchymal transition (EMT), metastatic progression or the breast cancer stem cell phenotype, among others.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…The last decade has unraveled multiple associations of m 6 A with different aspects of breast tumorigenesis [32]. However, it is still unclear whether this chemical mark contributes to tumor suppression or promotes oncogenicity.…”
Section: Introductionmentioning
confidence: 99%